Sierra Leone Rapid Damage and Loss Assessment of August 14th, 2017 Landslides and Floods in the Western Area - World Bank Group (World Bank, Washington, DC, 2017)
Sierra Leone is situated on the West Coast of Africa and is one of the poorest countries in Sub-Saharan Africa and globally, with a per capita gross domestic product of USD 684 in 2015. It is ranked 179 out of 188 countries on the United Nations 2016 Human Development Index, and chronic malnutrition is still on the rise with 44 percent of children below 5 being stunted in 2010, up from 40 percent in 2005. Per capita gross domestic product (GDP) stagnated after independence in 1961, contracted by 3.4 percent on average during the civil war (1991-2001) and increased by an average of 5.9 percent from 2002 to 2014. The country was severely affected by twin shocks in 2014, the Ebola Virus Outbreak and the downturn of international prices of iron ore, the combination of which caused the economy to contract by more than 20 percent, plunging the country into economic and social turmoil. It has yet to recover. Agriculture is the main source of livelihood in Sierra Leone, particularly for the poor, contributing almost 50 percent of increases in GDP between 2001 to 2014. The flooding hazard in and around Freetown is found along and adjacent to the many watercourses that run through the city, draining the hilly areas. These watercourses change as they run downslope. Nearer the top, narrower valleys tend, after rain, to produce very turbulent fast-flowing water flows. As the rivers descend to the lower elevations of the coastal plain, the river channels widen and flows slow. At the mouths of the rivers, the channels open out into a low-lying, delta shaped alluvial floodplain and mudflats.